The Legality of Copyright of Artificial Intelligence Video Works on the SORA Platform Under Intellectual Property Law - Vincentius Pieter Noehveltino Bonitu Suri; Andry Setiawan (Law Research Review Quarterly, 2026)
The rapid emergence of Generative artificial intelligence, particularly the Sora platform's text-to-video capabilities, presents unprecedented challenges to the anthropocentric foundations of Indonesian copyright law. The main problem lies in the legal vacuum regarding the authorship and originality of AI-generated videos, as traditional frameworks strictly require a human's personal touch and intellectual contribution. This research aims to analyze the copyright legality of Sora-generated videos under Law Number 28 of 2014 concerning Copyright, compare the regulatory approaches of the United States and China, and evaluate the juridical consequences of this legal vacuum on the creative industry. This study employs a normative legal research method using statutory, conceptual, and comparative approaches. The findings reveal that under Indonesian law, videos generated purely by AI operate outside the scope of copyright and fall into the Public Domain unless a substantial human intervention is proven. Comparatively, the US strictly denies AI authorship based on the idea-expression dichotomy, whereas China progressively recognizes complex prompt engineering as a protectable human intellectual investment. The study concludes that Indonesia must navigate a middle-ground approach by officially recognizing the category of "AI-assisted Works." To prevent industry disruption such as copyright trolling and the spread of low-quality content, the government is urged to update current regulations and establish a specific verification test that requires creators to submit evidence of their iterative creative process and editorial control as a prerequisite for copyright protection.